2016
DOI: 10.1002/hbm.23197
|View full text |Cite
|
Sign up to set email alerts
|

Network dynamics during the different stages of hallucinations in schizophrenia

Abstract: The majority of patients with schizophrenia suffer from hallucinations. While the triple-network model, which includes the default mode network (DMN), the central executive network (CEN) and the salience network (SAL), has recently been applied to schizophrenia, how this framework could explain the emergence of hallucinations remains unclear. Therefore, complementary brain regions that have been linked to hallucinations, such as the left hippocampus, should also be considered and added to this model. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
84
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 70 publications
(106 reference statements)
14
84
2
Order By: Relevance
“…Interestingly, this PC revealed activation of the brain regions involved in auditory hallucination‐related processes and in self‐other distinction, such as the right temporo‐parietal junction (Jardri et al, ; Decety & Lamm, ; Plaze et al, ), together with a deactivation of key nodes of the DMN, including the posterior cingulate cortex, medial prefrontal cortex, medial temporal cortex, and lateral parietal cortex (Buckner, Andrews‐Hanna, & Schacter, ). Our results appeared fully compatible with recent fMRI‐capture findings demonstrating that aberrant activations of speech‐related areas concomitant with hallucinatory experiences follow complex interactions between ICNs, such as the DMN and the CEN (Lefebvre et al, ). A disengagement of the DMN during goal‐directed behaviors has been seminally evidenced in the resting‐state literature (Fox et al, ; Lefebvre et al, ; Raichle et al, ), and similar mechanisms might be involved in hallucinatory occurrences (Jardri et al, ; Leroy et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, this PC revealed activation of the brain regions involved in auditory hallucination‐related processes and in self‐other distinction, such as the right temporo‐parietal junction (Jardri et al, ; Decety & Lamm, ; Plaze et al, ), together with a deactivation of key nodes of the DMN, including the posterior cingulate cortex, medial prefrontal cortex, medial temporal cortex, and lateral parietal cortex (Buckner, Andrews‐Hanna, & Schacter, ). Our results appeared fully compatible with recent fMRI‐capture findings demonstrating that aberrant activations of speech‐related areas concomitant with hallucinatory experiences follow complex interactions between ICNs, such as the DMN and the CEN (Lefebvre et al, ). A disengagement of the DMN during goal‐directed behaviors has been seminally evidenced in the resting‐state literature (Fox et al, ; Lefebvre et al, ; Raichle et al, ), and similar mechanisms might be involved in hallucinatory occurrences (Jardri et al, ; Leroy et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…By replicating previous findings, these results provide further support for the existence of anti‐correlation between the DMN and sensory cortices during AVH experiences and of a central role of DMN dynamics in these phenomena (Alderson‐Day et al, ; Lefebvre et al, ). This finding allows us to add the anti‐correlation of DM‐/AVH‐related time courses as a complementary selection criterion for the component of interest in the “2S” method (Lefebvre et al, ). These findings reinforce the consistency of the method as applied to fMRI capture of hallucinations.…”
Section: Discussionsupporting
confidence: 86%
“…Another possible explanation for the observed dissociation between structural and functional connectivity is that functional connectivity compensates the reduced integrity of structural connections [Fornito et al, ; Honey et al, ], at least during the early stages of the disease. Indeed, while preserved functional connectivity was evident in the present study, which mostly included patients with 22q11DS at‐risk but not diagnosed with schizophrenia, this is not the case in schizophrenic patients [Chang et al, ; Iwabuchi et al, ; Lefebvre et al, ; Manoliu et al, ; Moran et al, ; Orliac et al, ; Palaniyappan et al, ]. This may suggest that the structure‐function relationship may change at different stages of the disease, and that functional connectivity impairments would correspond to later, more severe stages.…”
Section: Discussionmentioning
confidence: 64%
“…However, we did not observe a relationship between altered triple network connectivity and psychotic symptoms in patients with 22q11DS. Of note, the studies conducted in schizophrenic patients reported functional connectivity impairments related to psychotic symptoms [Lefebvre et al, ; Manoliu et al, ], while no evidence exists of a relationship between triple network structural dysconnectivity and the symptomatic profile [Chen et al, ; Iwabuchi et al, ]. As discussed in the previous paragraphs, functional connectivity seems to be preserved in patients with 22q11DS, and this might explain the lack of correlations with psychotic symptoms in this population.…”
Section: Discussionmentioning
confidence: 90%